THE RELATIONSHIP OF SIBLING RIVALRY EVENTS WITH COPING MECHANISMS OF SCHOOL AGE CHILDREN AT MI AL HUDA KARANGPANDAN - Okta Fiana, Dwi; Dwilestari Puji Utami, Ratih; Indri Hapsari, Happy (Universitas Kusuma Husada Surakarta, 2025)
Sibling rivalry is a common phenomenon in families that often occurs. Sibling rivalry is competition or rivalry, jealousy and anger between siblings. Sibling rivalry can affect school age children's coping mechanisms. Coping mechanisms are ways that children use to deal with stress and conflict in certain situations. Factors that influence sibling rivalry include parental attitudes, positional factors, gender and age differences. Coping mechanisms are important to support the adaptation process. Children who are able to adapt well will support an adaptive coping process. This study aims to determine the relationship between the occurrence of sibling rivalry and coping mechanisms of school-age children at MI Al Huda Karangpandan This quantitative study used a descriptive correlational approach with a cross-sectional design. This study involved 59 school-age students who were selected using cluster random sampling technique. The results showed that the majority of respondents, 42.4%, had high sibling rivalry and 74.6% had maladaptive coping mechanisms. The results of the study using the Eta correlation test obtained a p-value of 0.027 (p < 0.05), so this means that Ho is rejected and Ha is accepted, which means that there is a relationship between sibling rivalry and coping mechanisms of school-age children at MI Al Huda Karangpandan. While the strength of the relationship between the 2 variables is shown in the Eta value, which is 0.746 or has a strong relationship strength. Based on this research, parents and schools can pay more attention to approaches in helping children to reduce and overcome sibling rivalry.